2015
DOI: 10.3892/mmr.2015.3857
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of quercetin in a mouse model of brain ischemic/reperfusion injury via anti-apoptotic mechanisms based on the Akt pathway

Abstract: Abstract. The present study provided experimental evidence for the neuroprotective effects of quercetin using a rat model of global brain ischemic/reperfusion (I/R) injury. Pre-treatment with quercetin (5 or 10 mg/kg orally (p.o.); once daily) induced a dose-dependent reduction in I/R-induced hippocampal neuron cell loss, with 10 mg/kg/day being the lowest dose that achieved maximal neuroprotection. Administration of 10 mg/kg quercetin over at least 3 days prior to I/R was required to improve the survival rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 36 publications
5
25
0
Order By: Relevance
“…These studies exhibited their beneficial effect as neuroprotective agents. Among these compounds are quercetin [41], gallic acid [42, 43], catechin [44], and emodin [45]. Additionally, many phenolic compounds were previously reported as neuroprotective [46], whereas P. austroarabica extract is considered to accumulate a considerable amount of phenolic constituents.…”
Section: Discussionmentioning
confidence: 99%
“…These studies exhibited their beneficial effect as neuroprotective agents. Among these compounds are quercetin [41], gallic acid [42, 43], catechin [44], and emodin [45]. Additionally, many phenolic compounds were previously reported as neuroprotective [46], whereas P. austroarabica extract is considered to accumulate a considerable amount of phenolic constituents.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin has been shown to induce several positive effects in CVS such as blood pressure lowering effects (Perez-Vizcaino et al 2009, Larson et al 2012 or protective effects on hearts exposed to I/R injury (Ikizler et al 2007, Bartekova et al 2010. It has been also documented that quercetin exerts protective effects in non-cardiac I/R models such as renal (Singh et al 2004, Chen et al 2014), brain (Yao et al 2012, Lei et al 2015) or liver (Su et al 2003, Tokyol et al 2006 ischemia. It has been demonstrated that the efficiency of certain protective interventions against I/R injury may be age-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Root of A. speciosa rich with quercetin, caffeic acid and coumarin. Many investigators claim that quercetin possesses the anti-stroke activity 55,56,57 . Apart from this, coumarin and its derivatives compounds also attenuated the cerebral ischemic/reperfusion injury 58,59,60 .…”
Section: Discussionmentioning
confidence: 99%